The circular economy business model: Examining consumers' acceptance of recycled goods - Cristina Calvo-Porral; Jean-Pierre Lévy-Mangin (Administrative Sciences, 2020)
The circular economy strategy supports the transformation of the linear consumption model into a closed-production model to achieve economic sustainability, with the consumers' acceptance of circular products being one of the major challenges. Further, one important aspect of product circularity remains unexplored, such as the consumers' purchase intention of recycled circular goods. In this context, the present study proposes and tests a conceptual model on consumers acceptance of recycled goods through PLS Structural Equation Modeling (PLS-SEM), based on the data obtained from 312 respondents. Results indicate that the positive image of circular products is the most important driver of consumers' acceptance, followed by the product perceived safety. This study provides an empirical foundation for the important role of consumers in circular economy business models through the examination of consumers' acceptance of recycled goods.
Keywords: 350; circular economy; consumer acceptance; recycled products; sustainability